Dampak Ekologi, Ekonomi dan Sosial Pembangunan Pelabuhan Kaliadem Muara Angke - Dwi Ayu Setiani; Hadi Supriyanto; Ria Puspita (ECOTAS, 2022)
Ecological-based development is a sustainable development that does not only have an impact on the economy but also pays attention to the environmental conditions of natural resources, the reclamation of the Muara Angke port has an impact on the livelihoods of fishermen around the coast. This study aims to find out how the port of Muara Angke has an impact on the economy of coastal communities not only on the economy but also on environmental aspects. This study uses literature study sourced from documents, journals and articles. The results of this study found that the construction of the Muara Angke port has not fully paid attention to the ecological aspects of this because of environmental conditions such as floods, puddles, and slum settlements in the coastal area of ??Muara Angke.